Rol de enfermería y su incidencia en niños menores de 2 años con esquema de vacunación incompleto en el Centro de Salud Puebloviejo octubre 2018- abril 2019 - Cerezo Alvarez, Meysi Lilibeth (2019)
The present research project makes an analysis of the different causes that lead to children under two years of the Puebloviejo Health Center do not comply with the vaccination scheme giving relevance to immunization since this is an effective method for the prevention of diseases and it has been shown that the morbidity and mortality rate has decreased. In Ecuador, the main cause of morbidity and mortality caused by noncommunicable diseases is produced by incomplete vaccination scheme. The main province with the highest rate of incomplete vaccination is Morona Santiago, which has 88.7% of the cases, followed by the province of Napo with 53.9%, continues with Cañar with 52% and Pastaza with 40.3%. Our objective with this project is to determine how it affects the non-compliance of the vaccination scheme in children under 2 years old in the Puebloviejo health center, we use research methods such as: logical and inductive history, with a quantitative modality, for the execution data collection we obtain through surveys directed at mothers of children and through observation. Our collection of subjects to investigate is 64 children with incomplete vaccination scheme. Through the survey it was possible to obtain the high level of misinformation of the mothers about the vaccination program for their children.Most of the population is in an uneducated level which represents 83%, which is notable that the highest percentage have a deficit in school readiness, so we conclude that the little guidance on the vaccination scheme is the cause of its breach.